Identification of Bali Island Deformation Based on Recorded GPS Data, Using GAMIT/GLOBK Software 10.6 - Suarbawa, Komang Ngurah; Sukarasa, I Ketut; Riyono, Elvin (BULETIN FISIKA; Vol 22 No 1 (2021): BULETIN FISIKA February Edition, 2020)
Research on the tectonic activity of the island of Bali has been carried out which aims to identify and determine the direction of the deformation movement of the island of Bali. The research was conducted using local GPS data recorded at eleven observation points on the island of Bali. Data processing was carried out using GAMIT / GLOBK 10.6 SOFTWARE and several supporting software such as teqc to test the quality of GPS and GMT recording data to plot the processed data. The results showed that there was a shift in the observation point which indicates tectonic activity on the island of Bali. The point shift pattern shows a shift that tends to be east to southeast. The deformation pattern is thought to have occurred due to tectonic plate activity in the eastern and southern parts of the island of Bali.